PENGEMBANGAN KEMAMPUAN DAN KOMITMEN BUMDES BERBASIS PARTISIPASI MASYARAKAT PADA BUMDES DI KABUPATEN TUBAN - Tawakkal, George Towar Ikbal; Wanto, Alfi Haris; Rahman, Khalid; Rohman, Ahmad Zaki Fadlur (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
BUMDes is institutionalized in regulations at the central level. Although its presence is not mandatory, BUMDes is expected to improve the welfare of village communities. Many villages already have BUMDes, including Plajan Village, Tuban Regency. Several obstacles that focus on participation and human resource capabilities have caused BUMDes in the village to not run. This service method is implemented in the form of a training workshop, by providing material on institutional arrangements or BUMDes management and strengthening the ability to capture business opportunities for BUMDes managers. The results of the evaluation before the workshop for participants showed that managers did not have sufficient understanding of BUMDes regulations and management, and were weak in capturing business opportunities. After the training, the participants improved in their understanding, but the results of the evaluation one month after the workshop showed that there was no follow-up by them in the village government. This means that the commitment of BUMDes managers is also weak